(untitled) (Confluenţe Bibliologice, 2017)
ABRM Annual Conference „We Transform Libraries – We Transform Communities‘‘ on November 10, 2017 was held at Alecu Russo Balti State University. There were 110 librarians from the National Library System in Moldova (national, university, specialized, public, college, center of excellence, vocational and school libraries). The conference was dedicated to the work of libraries in national and international projects, their involvement in community transformation, the modernization of librarians’ skills.